Building Coalitions: Networking - Vicki Braddy; Elizabeth B. Bolton; Lisa Guion (EDIS)
This document is FY503, Part 11 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.